2021
DOI: 10.3389/fnmol.2021.610857
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Reversible Development of Axonal Varicosities: A New Form of Neural Plasticity

Abstract: Axonal varicosities are enlarged, heterogeneous structures along axonal shafts, profoundly affecting axonal conduction and synaptic transmission. They represent a key pathological feature believed to develop via slow accumulation of axonal damage that occurs during irreversible degeneration, for example in mild traumatic brain injury (mTBI), Alzheimer's and Parkinson's diseases, and multiple sclerosis. Here this review first discusses recent in vitro results showing that axonal varicosities can be rapidly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 82 publications
(166 reference statements)
1
26
0
Order By: Relevance
“…Such S1 proteininduced endolysosome dysfunction could also disrupt the transport of synaptic vesicle precursors, lysosomes and autophagic components within both the axon and dendrites. Our results show that S1 protein enlarged lysosomes within these varicosities; a finding similar to that observed in Alzheimer's disease (Gowrishankar et al, 2015;Gu, 2021). However, further mechanistic investigations are warranted to understand the exact nature of these structures and how they form.…”
Section: Discussionsupporting
confidence: 83%
“…Such S1 proteininduced endolysosome dysfunction could also disrupt the transport of synaptic vesicle precursors, lysosomes and autophagic components within both the axon and dendrites. Our results show that S1 protein enlarged lysosomes within these varicosities; a finding similar to that observed in Alzheimer's disease (Gowrishankar et al, 2015;Gu, 2021). However, further mechanistic investigations are warranted to understand the exact nature of these structures and how they form.…”
Section: Discussionsupporting
confidence: 83%
“…We speculate that the neurological consequences of more densely packed WM might include reduced efficiency of electric signal transport or less effective extracellular matrix; however, preclinical studies investigating this possibility in 22q-del models have not yet been done. Indeed, previous research in (mild) traumatic brain injury and neurodegenerative disorders has suggested that axonal swellings or beading translate into disturbed axonal conduction and synaptic transmission [ 105 ]. However, we acknowledge that our interpretation is speculative, and future studies are needed to explore the underlying neurobiological basis of WM abnormalities in 22q11.2 CNV carriers.…”
Section: Discussionmentioning
confidence: 99%
“…To really understand the origin and progression of decay, we would need pathological timelines of events-but such systematic descriptions are rare (e.g., Spencer & Schaumburg, 1977a, 1977b probably as manifestations of a major pathway of CNS axonal death' (Coleman, 2005). Usually, these swellings are characterised by the accumulation of organelles and disorganisation or even disappearance of the cytoskeleton (Figure 2b, top; e.g., Berard-Badier, Gambarelli, Pinsard, Hassoun, & Toga, 1971;Bridge et al, 2009;Fassier et al, 2013;Fiala, Feinberg, Peters, & Barbas, 2007;Havlicek et al, 2014;Jellinger & Jirasek, 1971;Probst et al, 2000;Seitelberger, 1971;Tarrade et al, 2006;Yang et al, 1999); they are known to interfere with action potential propagation (Gu, 2021). (Figure 2a, top).…”
Section: Is There a Common Pathology?mentioning
confidence: 99%